Challenging Corruption in Asia : Case Studies and a Framework for Action - Bhargava, Vinay; Bolongaita, Emil (Washington, DC: World Bank, 2013)
At the economic level, corruption is seen as a contributing factor to the East Asian financial crisis. The crisis focused people's attention on the staggering impact of corruption, particularly in Indonesia, the Republic of Korea, and Thailand. The interlocking relationship of business and government were previously viewed as part of the way of doing business and practicing politics-a useful partnership crucial to strategic policymaking. As one scholar noted, "Not too many years ago, the economic successes of the countries of East Asia were attributed by some observers to a presumably positive impact of corruption in facilitating decisionmaking". Many actors justified questionable practices by explaining them to be necessary conditions for rapid economic development. Today those specific practices constitute the problematic areas of corruption. At the political level, corruption has risen in recent years in national agendas because of its role in political developments. At one point the heads of government themselves of Indonesia, the Philippines, and Thailand were in the dock on corruption-related charges. Peaceful populist protest forced the Philippine president, Joseph Estrada, to step down in January 2001. In July 2001 Indonesia's parliament removed President Abdurrahman Wahid from office partly because of corruption allegations. Thaksin Shinawatra, prime minister of Thailand, was indicted by the National Counter-Corruption Commission but was eventually acquitted in a controversial decision by the country's Constitutional Court. In 2002 the convictions of two sons of President Kim Dae-Jung of the Republic of Korea on corruption charges tarnished the president's achievements. Other high-level political leaders have also been convicted recently on corruption-related charges in China, Indonesia, the Philippines, and Thailand.